Flexural properties of leucite and lithium disilicate ceramic materials after repeated firingst - GÖZNELİ, RİFAT; ÖZKAN, YASEMİN (ELSEVIER TAIWAN, 2014)
Background/purpose: Pressable all-ceramic materials are widely used in dentistry. Determining the effect of repeated firing on flexural strength will help to improve these materials so that they can remain resistant to fracture in restorative work. The aim of this study was to determine the change in the flexural strength of pressable all-ceramic materials after repeated firings, which may be unavoidable when color and shape corrections are necessary for use in dental restorations. Materials and methods: Forty disc specimens (15.5 mm x 2.1 mm) were prepared for each of four pressable ceramic materials (Empress 2, Finesse, Cergo, and Evopress) according to the manufacturers' instructions. Each group of specimens was tested for biaxial flexural strength (piston on three balls test) after the first (n = 10), third (n = 10), fifth (n = 10), and seventh (n = 10) firing periods. The data were analyzed using one-way analysis of variance. The Tukey multiple comparison test was then used to compare the strength of the different materials, and the Newman-Keuls multiple comparison test was used to compare the strength at each firing interval measured (alpha = 0.05). Results: The strengths of all of the pressable ceramic materials were decreased by repeated firings, especially after the seventh firing period, the only case in which the decrease was statistically significant. The flexural strength of the leucite-reinforced ceramic (Cergo) after the seventh firing was significantly lower than after the first firing (P = 0.04). The other materials were not significantly affected by repeated firings (P > 0.05). Conclusion: The number of firings does not appear to significantly affect the flexural strength of pressable all-ceramic materials. Copyright (C) 2013, Association for Dental Sciences of the Republic of China. Published by Elsevier Taiwan LLC. All rights reserved.
Keywords: flexural strength; leucite; lithium disilicate; repeated firing; 4 DENTAL CERAMICS; FRACTURE-TOUGHNESS; STRENGTH; PORCELAIN; RELIABILITY; ALUMINA; MICROSTRUCTURE; ZIRCONIA; LAYER; BOND